(untitled) (Eurasian Medical Research Periodical, 2026)
Oxidative stress is a universal mechanism of hepatocyte damage in chronic hepatitis C (CHC). Manganese superoxide dismutase (SOD2) is the key mitochondrial antioxidant enzyme. The Ala16Val polymorphism (rs4880) affects enzyme import into the mitochondrial matrix. This study aimed to evaluate the association of SOD2 Ala16Val with liver cirrhosis (LC) formation in CHC patients and to assess its relationship with disease severity markers and esophageal varices (EV)